2016
DOI: 10.1038/srep37238
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal auditory preferences in piglets differ according to maternal emotional experience with the same sounds during gestation

Abstract: Prenatal sensory experience, notably auditory experience, is a source of fetal memories in many species. The contiguity between sensory stimuli and maternal emotional reactions provides opportunity for associative learning in utero but no clear evidence for this associative learning has been presented to date. Understanding this phenomenon would advance our knowledge of fetal sensory learning capacities. In the present study we tested the hypothesis that sounds (human voice) broadcast to pregnant sows while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…As DeCasper et al have described (Busnel et al 2017, DeCasper & Fifer 1980, this preference for the maternal voice over another woman's likely subserves bonding while transnatal memory for language-specific properties may undergird language development. A recent novel experiment (Tallet et al 2016) extended prenatal auditory learning, asking whether pairing prenatal auditory voice exposure with a maternal aversive versus positive experience would influence postnatal behavior when the familiar voice was heard. Late-gestation pregnant sows underwent soft brushing versus electrical prodding manipulation while hearing a tape-recorded voice.…”
Section: Maternal Distress Gets Under Fetal Skin Mechanisms: How Matementioning
confidence: 99%
“…As DeCasper et al have described (Busnel et al 2017, DeCasper & Fifer 1980, this preference for the maternal voice over another woman's likely subserves bonding while transnatal memory for language-specific properties may undergird language development. A recent novel experiment (Tallet et al 2016) extended prenatal auditory learning, asking whether pairing prenatal auditory voice exposure with a maternal aversive versus positive experience would influence postnatal behavior when the familiar voice was heard. Late-gestation pregnant sows underwent soft brushing versus electrical prodding manipulation while hearing a tape-recorded voice.…”
Section: Maternal Distress Gets Under Fetal Skin Mechanisms: How Matementioning
confidence: 99%
“…Piglets are able to recognize a human voice heard during the sow's pregnancy. They appear distressed when that human voice was previously associated with a negative maternal emotional state during pregnancy (Tallet, Rakotomahandry, Guérin, Lemasson, & Hausberger, 2016). Transnatal transmission has been demonstrated mainly for humans' chemical perception and, to some extent, for their auditory perception, but more information is still needed for both these modalities and others.…”
Section: Promoting Quantitative Behavioral Observationsmentioning
confidence: 99%
“…Recent studies have reported that some animals have an efficient visual (cattle: [6]; sheep: [7]; horses: [8]; and dogs: [9]) and auditory recognition of their conspecifics (cats: [10]; dogs: [11,12]; cattle: [13]; pig: [14]; and horses: [15]). Several species of domestic mammals are also able to discriminate between familiar and unfamiliar humans (cats: [16]; pigs: [17]; cattle: [18]; and horses: [4]) and form a memory of specific persons that influence their reactions in subsequent interactions (pigs: [19]; and horses: [20,21]). Moreover, a growing body of literature has demonstrated that domestic species recognize human faces (dogs: [5]; sheep: [22,23]; horses: [24]) and voices (cats: [3]; horses: [20,21]; pig: [19,25]; and dogs: [26]).…”
Section: Introductionmentioning
confidence: 99%
“…Several species of domestic mammals are also able to discriminate between familiar and unfamiliar humans (cats: [16]; pigs: [17]; cattle: [18]; and horses: [4]) and form a memory of specific persons that influence their reactions in subsequent interactions (pigs: [19]; and horses: [20,21]). Moreover, a growing body of literature has demonstrated that domestic species recognize human faces (dogs: [5]; sheep: [22,23]; horses: [24]) and voices (cats: [3]; horses: [20,21]; pig: [19,25]; and dogs: [26]). Animals not only identify conspecifics and humans through separate sensory modalities (e.g., cats: [3]; dogs: [5]; goats: [27]; sheep: [22,23]; cattle: [6]; and cheetahs: [28]) but they are also capable of integrating identity cues from multiple sensory modalities to recognize them (dogs: [26,29]; horses: [30,31]; goats: [32]; rhesus monkeys: [2,33]; crows: [34], and cats: [35]).…”
Section: Introductionmentioning
confidence: 99%